2007
DOI: 10.1016/j.phrs.2007.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the endocannabinoid system: Therapeutic potential against cocaine dependence

Gianluigi Tanda

Abstract: Dependence on cocaine is still a main unresolved medical and social concern, and in spite of research efforts, no pharmacological therapy against cocaine dependence is yet available. Recent studies have shown that the endocannabinoid system participates in specific stages and aspects of drug dependence in general, and some of this evidence suggests an involvement of the cannabinoid system in cocaine effects. For example, cocaine administration has been shown to alter brain endocannabinoid levels, and the endoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 156 publications
(192 reference statements)
0
17
0
Order By: Relevance
“…Further, a preliminary report indicated that RTI-371 blocked cocaine-induced locomotor stimulation (Navarro et al, 2009). Finally, because both RTI-371 and JHW007 produced positive-allosteric modulation of CB1Rs, and CB1Rs have been implicated in the neurobiology of cocaine addiction (see Tanda, 2007 for review), Navarro et al (2009) suggested that the atypical effects of both of these compounds were a result of a positive allosteric modulation of CB1Rs, as indicated by the increased efficacy of the CB1 agonist, CP 55940 in a calcium mobilization assay. From those results Navarro et al suggested that enhanced endocannabinoid neurotransmission may contribute to the cocaine-antagonist effects observed with these atypical DAT inhibitors.…”
Section: Effects Of Atypical Dat Inhibitorsmentioning
confidence: 99%
“…Further, a preliminary report indicated that RTI-371 blocked cocaine-induced locomotor stimulation (Navarro et al, 2009). Finally, because both RTI-371 and JHW007 produced positive-allosteric modulation of CB1Rs, and CB1Rs have been implicated in the neurobiology of cocaine addiction (see Tanda, 2007 for review), Navarro et al (2009) suggested that the atypical effects of both of these compounds were a result of a positive allosteric modulation of CB1Rs, as indicated by the increased efficacy of the CB1 agonist, CP 55940 in a calcium mobilization assay. From those results Navarro et al suggested that enhanced endocannabinoid neurotransmission may contribute to the cocaine-antagonist effects observed with these atypical DAT inhibitors.…”
Section: Effects Of Atypical Dat Inhibitorsmentioning
confidence: 99%
“…Indeed, the extant literature on treatment for psychostimulant drug abuse is expansive, and includes cognitive/behavioral therapy (e.g., for reviews, see Knapp et al, 2007;Shearer, 2007) and pharmacotherapies (e.g., for reviews, see Bubar and Cunningham, 2006;Dwoskin et al, 2006;Lile, 2006;Tanda, 2007, Withers et al, 1995. The latter of which include antidepressants (Dwoskin et al, 2006), serotonin modulation (Bubar and Cunningham, 2006), and endocannabinoid modulation (Tanda, 2007), to name a few. One may theorize that cessation of psychostimulant drug abuse would be beneficial for the HIV-infected population; so in essence, may serve as an intervention in the progression of HIV-related symptomatology.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…In addition to its well-known role in stress and anxiety 128 , the eCB system has been implicated in addiction-related processes and behaviors 129 . In fact, drugs of abuse and natural rewards are known to alter brain eCB content 130 .…”
Section: What Are the Molecular Mediators Of Addiction Pathology?mentioning
confidence: 99%